Kreativitas Petani Padi dalam Mengelola Lahan Rawa Pasang Surut di Kecamatan Tamban Kabupaten Barito Kuala - Anggelina Puspitasari; Mariani Mariani; Luthfi Fatah (Universitas Lambung Mangkurat, 2011)
Tidal swampy areas are known as fragile ecosystem. Farmers’ creativity is needed in order to transform this marginal area to be high productivity cultivation area. The research objectives are: (1) to observe the paddy farmers’ creativity level, and (2) to observe the relationship between farmers’ creativity and particular factors related to creativity, such as: education, experience, income, cosmopolity, and extension intencity. By using survey method, 60 farmers from two different areas (based on tidal flooding types) were purposively taken as respondents. The result showed that farmers’ creativity to manage their tidal swampy ricefileds was catagorized as medium level. There was a relationship between the factors of experience, income, cosmopolity, and extension intencity with farmers’ creativity level. On the other hand, a negative correlation on formal education and no correlation on informal education were founded.